A seasonal source and sink of nitrous oxide in mangroves: Insights from concentration, isotope, and isotopomer measurements. (1st October 2018) - Murray, Rachel; Erler, Dirk; Rosentreter, Judith; Maher, Damien; Eyre, Bradley
Abstract: Mangrove forests can be a source or a sink of nitrous oxide (N2 O) to the atmosphere, but seasonal mangrove N2 O dynamics are not well understood. We used continuous high-resolution N2 O concentration data to construct seasonal budgets of N2 O in two tropical mangrove-lined creeks for both the wet and dry seasons. Furthermore we used N stable isotope analysis to constrain the pathways of N2 O production and consumption within these creeks. Calculated water-air fluxes were within a range typical of undisturbed mangroves, however obvious seasonal differences in N2 O dynamics were observed at the two sites. The mangrove systems were a net source of N2 O to the atmosphere during the dry season and a net sink during the wet season. In the wet season we propose that increased allochthonous carbon enhances N2 O consumption by denitrification. Combining the seasonal fluxes, the Fitzroy mangrove system, which received a continual input of allochthonous nitrate (NO3 − ), was a net source of N2 O, while the Burdekin mangrove system was close to a net N2 O balance. Interpreted in the context of DIN and N2 O concentrations, the N2 O isotopic values observed in the dry season point to fungal denitrification as the most likely pathway of N2 O production. This study shows that subtle shifts in seasonal nutrient supply regulate mangrove N2 O production and consumption.